Behavioral and physiological determinants of food choice and consumption at sensitive periods of the life span, a focus on infants and elderly. (April 2018) - Schwartz, Camille; Vandenberghe-Descamps, Mathilde; Sulmont-Rossé, Claire; Tournier, Carole; Feron, Gilles
Abstract: Infancy and old age are two crucial periods in the human life span. During infancy, early exposure to a large variety of flavor and texture plays a key role in shaping food acceptability and later eating habits. In elderly people, food history is one of the major determinants of food choice. In both populations, sensory and oral motor skills are important determinants of food choice. During eating, the formation of a food bolus that can be safely swallowed is a complex oral process, and the oral capacity to perform this process impacts directly food acceptability or rejection both in infants or elderly. Food liking in elderly is also impacted by chemosensory impairment. The specificities of these populations imply to conduct active researches aiming at proposing novel food products better adapted to them but also guidelines to caregivers who are widely involved in their feeding practices. Highlights: Infancy and old age are crucial periods for food choice and behavior in human. Early repeated exposure to a variety of food is a major determinant of food choice and behavior in infants. Food choices and preferences in infants and elderly depend largely on motor oral skills. There is a need to propose innovating food products to these specific populations.